ESTIMASI FUNGSI KONSUMSI MASYARAKAT DI PROVINSI JAMBI - Daffa Setya Ulhaq; Syamsurijal Tan; Rahma Nurjanah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the development and the influence of income, inflation, interest rates, and previous-year consumption on household consumption in Jambi Province during the period 2000–2024. The study uses secondary data in the form of time series obtained from the Central Bureau of Statistics (BPS) and Bank Indonesia. The analysis was conducted using multiple linear regression with the EViews application. The results show that, in general, household consumption in Jambi Province has increased, with an average growth rate of 7.58% per year. Based on the regression results, income and previous-year consumption variables significantly affect household consumption, while inflation and interest rates have no significant effect. This indicates that rising income levels and past consumption habits are the main factors influencing household consumption patterns in Jambi Province.